Long-term impact of post COVID-19 pandemic quarantine on eating habits changes among adult residents of Riyadh, Saudi Arabia - Al-Tannir, Mohamad; AlFayyad, Isamme; Altannir, Mona; Alosaimi, Arwa; Alonazi, Afrah; Alqarni, Afnan (Frontiers in Nutrition, 2023)
Background: COVID-19 outbreak and quarantine measures clearly had an impact on the population's eating habits-related behavior. Objective: This study aimed to explore the long-term impact of the COVID-19 pandemic and physical quarantine on eating habits after quarantine among Riyadh city residents, Saudi Arabia. A cross-sectional study was conducted through an online survey between December 2022 and April 2023 on a convenient sample of Saudi adults in Riyadh, Saudi Arabia. A valid questionnaire was used to measure study outcomes. A comparison between dietary habits before and after COVID-19 was performed to identify the changes in dietary habits. Results: 1451 Saudi adults residing in Riyadh completed the online survey. The majority (88.6%) of the respondents reported changes in dietary habits after COVID-19. About 50% had 1-3 dietary habits changes and slightly more than one-third had 4-7 dietary habits change. About 33.8% of the participants reported stable weight during the COVID-19 pandemic. However, 40.9% reported weight gain, and 20.7% reported weight loss. The participants reported several unhealthy dietary changes most commonly eating fast food (33%), eating junk food/fast food due to boredom/distress/disappointment (29.8%), and high sugar such as sweet porridge, pastry, sweets, and chocolate (28.5%). On the other side, the participants showed healthy dietary habits such as having a balanced healthy ingredients diet (34.4%), an increase in the consumption of fruits and vegetables, and a decrease in the intake of junk foods (28.9%). Males were more likely to exhibit unhealthy dietary habits than females (Odd Ratio:1.43, p=0.038, CI: 1.02-2.02). Increasing age was associated with a reduction in the likelihood of exhibiting unhealthy dietary habits (OR: 0.98, p=0.011, CI: 0.96-0.99). Moreover, participants who reported stable weight or weight loss during COVID-19 were 0.29 (p=0.043, 0.09-0.96) and 0.34 (p=0.020, 0.07-0.79), respectively, less likely to have unhealthy dietary habits. Although healthy dietary habits have been reported in this study, such as consumption of fruits and vegetables, COVID-19 confinement has also led to negative dietary behaviors reflected by high consumption of fast/junk food and sugar intake resulting in weight gain, a potential adverse impact on the population wellbeing.